HUBUNGAN EFIKASI DIRI LANSIA TERHADAP VAKSIN COVID-19 DENGAN UPAYA LANSIA MENGIKUTI VAKSINASI COVID-19 - Agnes Novita; Reni Zulfitri; Ade Dilaruri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Background : SARS CoV-2 is the virus that causes Covid-19. Therefore of the Covid-19 vaccination could be preventive way of transmission of Covid-19 to the elderly. And it is affaceted by self-efficacy. This is also one of the important factors in improving health behavior in elderly. This study aims to analyze the relationship between the elderly’s self efficacy against the COVID-19 vaccine with the elderly’s efforts to follow the Covid-19 vaccination Methods : This research design uses a descriptive correlation design. The sample used was 99 respondents in the working area of the Puskesmas Rejosari, which were taken based on inclusion criteria with purposive sampling technique. The analysis used was bivariate and univariate analysis using the chi-square test. Results: The majority of nursing students were female as many as 109 students. Results : the majority of respondents were in the late elderly age stage (56-65 years) as many as 69 respondents (69,7%), female sex as many as 53 respondents (53,5%), the last education was high school as many as 38 respondents (38,4%), 45 respondents (45,5) marital status, namely married as many as 85 respondents (85,9%), and the most comorbid disease was hypertension as many as 43 respondents (43,3%). The description of the elderly,s self-efficacy for the Covid-19 vaccine is high as many as 54 elderly (54,5%), the description of the elderly efforts to follow the COVID-19 vaccination is good as many as 60 elderly (60,6%), and the results of chi square test ρ value < α (0,000 < 0,05). Conclusion : it can be concluded that H0 is rejected, meaning that there is a relationship between the elderly’s self-efficacy against the Covid-19 vaccine and the elderly’s participation in the Covid-19 vaccination. Keywords : Covid-19; elderly; self-efficacy; vaccination.